PENGARUH KUALITAS PRODUK WISATA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN (Studi pada Wisatawan Taman Wisata Kopeng Kabupaten Semarang) - Rizky Fajar Nugraha; Agus Hermani DS (Jurnal Ilmu Administrasi Bisnis, 2020)
Tourism is a service business sector that meets the spiritual needs of the general public. The tourism business is developing to meet the increasingly diverse needs of consumers. Taman Wisata Kopeng is one tourist attraction that presents a variety of tourism products and provides a variety of services in meeting the needs of tourists. In its development, Taman Wisata Kopeng has decreased the number of tourist levels because most tourists feel dissatisfied with tourism products and services provided, so tourists are reluctant to make a return visit or recommend Taman Wisata Kopeng to others. This study aims to determine the effect of tourism product quality and service quality on consumer satisfaction with Taman Wisata Kopeng tourists. This type of research used is explanatory research with a total sample of 100 respondents taken with a minimum criteria of age 17 years, was visiting Taman Wisata Kopeng, and had visited a maximum of the last 3 years. The sampling technique used was purposive sampling and accidental sampling. Data collection techniques used were questionnaires and Google forms with each totaling 50 respondents. The analytical tool used is SPSS 16.0 for Windows with validity test, reliability test, cross tabulation test, correlation coefficient test, coefficient of determination, simple and multiple regression analysis, and significance test (t test and F test). The results of this study indicate that the quality of tourism products partially has a positive and significant effect on consumer satisfaction with a coefficient of determination of 78.4%. The results of this study also show that service quality is partially positive and significant effect on customer satisfaction with a coefficient of determination of 75%. The quality of tourism products and service quality simultaneously have a positive and significant effect on consumer satisfaction.